Coffee Consumption to Reduce Liver Fibrosis - Yaldiera Utami; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2015)
As one of the most popular drink consumed daily, coffee is known to be good for health. One of the main substance found in coffee is caffeine. Several previous studies explained that caffeine found in coffee could act as hepatoprotective agents, and recently an antifibrotic agent. Since liver fibrosis is a fatal condition that could lead to liver cirrhosis and hepatocellular carcinoma, a lot of study were trying to find any alternatives to reduce fibrosis, one of them is coffee. Several studies have reported that coffee was significantly, able to reduce fibrosis process because of its caffeine which is found in coffee. Recently, some studies also reported that a non-caffeinated coffee also showed an antifibrotic effect. It is believed that several substances beside caffeine found in coffee were also played an important role in reduce liver fibrosis. By its cellular mechanism, coffee would be a new alternatives way to reduce liver fibrosis, and of course other chronic liver disease.